Design and performance evaluation of a PV interface system based on inductive power transfer - Ahmed Ragab; Mostafa I. Marei; Mohamed Mokhtar; Ahmed Abdelsattar (Institute of Advanced Engineering and Science, 2021)
This paper presents a photovoltaic (PV) based battery charger utilizing a wireless power transfer (WPT) interface system. The double-sided inductor-capacitor-capacitor (LCC) compensation network is utilized for the inductive power transfer (IPT) system. Because of nonlinear characteristics of the PV, the maximum power point tracking (MPPT) is achieved by controlling the phase displacement angle or the pulse width of the quasi-square pulse inverter connected to the transmitting coil of the IPT system. As a result, the power transferred to the secondary-side, which is connected to a battery bank, is regulated. The IPT-based PV interface system is designed to achieve zero voltage switching (ZVS) in the primary side at rated conditions to minimize the switching loss. Extensive simulation studies are carried out using EMTDC/PSCAD software to investigate the dynamic performance of the proposed IPT-based PV interface system.